Stylized facts of the business cycle: Universal phenomenon, or institutionally determined? - Vadim Kufenko; Niels Geiger (Universität Hohenheim, 2015)
This paper empirically investigates and theoretically reflects on the generality of the "stylized facts" discussed in business cycle analysis. Using OECD data for 1960 - 2010, the duration of business cycles as well as three models capturing core macroeconomic relations are estimated: based on the Phillips curve (the inflation-unemployment nexus), Okun's law (in the context of the relation between output growth and unemployment) and the inflation-output relation. Results are validated by relevant statistical tests. Observed durations vary from 4 to 8 years, and estimated coefficients differ in signs and magnitudes. Bearing these substantial variations in mind, an explanation of this heterogeneity is attempted by referring to proxies for various institutional variables for the goods, labour and money markets. The findings suggest that core coefficients in the relations, such as the slope of the Phillips curve, show significant correlation with some of these variables, but no uniform results are obtained. In the detailed theoretical discussion and interpretation it is thus argued that the notable differences between countries call the universality of the "stylized facts" into question, but also that these variations cannot be explained exhaustively by the institutional proxy variables employed here.
urn:nbn:de:bsz:100-opus-10897
Keywords: E02; E32; E39; F44; 330; business cycles; empirical analysis; institutions; stylized facts